The influence of body segment estimation methods on body segment inertia parameters and joint moments in javelin throwing - Köhler, Hans-Peter; Schüler, Axel; Quaas, Felix; Fiedler, Hannes; Witt, Maren; Roemer, Karen (Computer methods in biomechanics and biomedical engineering, 2024)
Calculated intersegmental moments are commonly used in analyzing throwing movements. The inverse dynamics (ID) results can vary due to the chosen set of body segment inertia parameters (BSIP). A multitude of methods to determine BSIP sets are available. The purpose of this study was to clarify the influence of different estimation methods on the BSIPs and the respective impact on the ID results in javelin throwing. Movement kinematics were recorded for ten male javelin throwers. Six different methods were used to estimate BSIP sets for the upper extremities of each thrower. Subsequently, ID results were obtained for each thrower and BSIP set. Results show variations between 8% and 120% between the BSIP sets, and maximum intersegmental moments varied between 6% and 21%, respectively. Joint-specific variations of intersegmental moments were observed as well as movement-specific variations within a joint related to the different BSIP sets. Furthermore, the influence of BSIP sets appears to be subject-specific as well, with observed variations between 9% and 18% - some athletes are better represented by the chosen methods than others. Hence, our study results suggest that the method to determine BSIP sets needs to be carefully chosen for calculating joint kinetics in throwing movements.